The industrial emissions trend and the problem of the implementation of the Industrial Emissions Directive (IED) - Conti, Marcelo Enrique (2015)
The European Integrated Pollution Prevention and Control (IPPC) came into force in 1996. In 2010, the EU Parliament approves the Industrial Emissions Directive (IED) that abrogates the IPPC directive. This directive lays down measures designed to regulate emissions arising from the activities of large European industries which recorded a constant decrease from 1990 to 2011. This trend refers especially to SOx/SO2 partly because of some technical changes such as the use of natural gas in the 1990s instead of coal and lignite. We can state that the 2008–2009 crisis is the most serious, affecting not only production but also other key economic sectors such as energy consumption. The aim of this work is to discuss relevant topics such as the current situation of industrial emissions in Europe and the trend of the industrial emissions since the promulgation of the directive. We also discuss the directive’s main application tools which are the best available techniques reference documents and the best available techniques that show some weakness. For instance, the “concentration approach” for measuring emissions does not comply with the environment and health problems, because it sets no limit to the production. We absolutely need to improve above mentioned tools if we want to reduce the emission of pollutants to acceptable levels, in spite of the European financial condition. The IPPC aimed at accelerating the reduction trend of the industrial emissions especially between 2000 and 2011. In conclusion, we still haven’t found evidences of significant results of its implementation as the emissions behaviour is also strongly influenced by the economy.